Competence Analysis of Human Resources on the Financial Performance of the Bireuen Regency Government - Jamaluddin, Jamaluddin; Triana, Neni; Saharuddin, Saharuddin (International Journal Labs, 2023)
Background: The ability and traits that a person possesses in the form of knowledge, skills, and behavioral attitudes required in the workplace are known as human resource competence (HR). Whether a region can adequately manage its domestic issues or not depends in part on the effectiveness of the government machinery. Aim: The purpose of this study was to empirically determine the effect of human resource competence on the financial performance of the Bireuen district government. Method: The variables used in this study are human resource competence as the independent variable and financial performance as the dependent variable. The approach used in this study is the quantitative by testing theories through measuring research variables and analyzing data with statistical procedures using SPSS V.22 for Windows. The type of data used in conducting this research is primary data obtained from the results of distributing questionnaires to BKPSDM Bireuen district. The sampling method in this study was saturated sampling method where the samples obtained were 46 respondents. Findings: The results stated that the direction of the influence of variable X on Y is positive, through the t test where tcount > ttable (9.380 > 2.015) thus Ha is accepted H0 is rejected. The human resource competency variable (X) is able to explain the effect on financial performance (Y) which is equal to 66.7% and the remaining 33.3% is influenced by other variables outside of this study.